If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 + -4x = -7x + -27 Reorder the terms: 60 + -4x = -27 + -7x Solving 60 + -4x = -27 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 60 + -4x + 7x = -27 + -7x + 7x Combine like terms: -4x + 7x = 3x 60 + 3x = -27 + -7x + 7x Combine like terms: -7x + 7x = 0 60 + 3x = -27 + 0 60 + 3x = -27 Add '-60' to each side of the equation. 60 + -60 + 3x = -27 + -60 Combine like terms: 60 + -60 = 0 0 + 3x = -27 + -60 3x = -27 + -60 Combine like terms: -27 + -60 = -87 3x = -87 Divide each side by '3'. x = -29 Simplifying x = -29
| Uk+uz=t | | (x+4y)(y+4x)=16 | | n^2-6n+3=2(3n-16) | | 2b^2+9=0 | | 20.6=(180+x)180 | | (3x^2-4xy^2)dx+(x^3-4x^2+12y^3)dy=0 | | 5x+5y=-21 | | 25x+10y+5z=55 | | 27h^3=216 | | 8x+6-20x= | | 16x+7=17x-1 | | 6(2+4)=4(3x+6) | | -7(x+1)-16=30+3 | | 2=52 | | 8-3j=I(5+j) | | 10-2(4x+12)=-x+4 | | 3=87 | | 4x(x+5)(x-12)=0 | | 16x+7+17x-1=180 | | 2rs-6r+4rs+12r-4s= | | (4+6)4=(3+2x^2)3 | | 10x+5=12x-13 | | 5a^3-8a^2+2a^3= | | 11(7)+8+14(7)=90 | | 9x(x+4y+5z)= | | 11(7)+8+14(7)=180 | | 3(6-2x)=-8 | | -6(2b+1)+(13b-1)=0 | | 2ax+3x=8 | | 1ax+3x=4 | | 7g^3=56 | | 2ax-3x=8 |